The effect of partial reinforcement on instrumental successive negative contrast in inbred Roman High- (RHA-I) and Low- (RLA-I) Avoidance rats - Cuenya, Lucas (2012)
Frustration is an emotional response that can be induced by the sudden devaluation of a reinforcer in the presence of greater reinforcement expectancies (e.g. instrumental successive negative contrast, iSNC). This emotional response seems to be similar to anxiety and can be attenuated by previous experiences of reward loss (e.g. partial reinforcement, PR, as opposed to continuous reinforcement, CR). In this study we used iSNC and PR procedures in order to compare the performance of two strains of rats psychogenetically selected on the basis of their emotional reactivity: the inbred Roman High- (RHA-I, low anxiety) and Low- (RLA-I, high anxiety) Avoidance rats. Animals were exposed to a straight alley, where they were changed from 12 pellets in the preshift phase (presented in 100% of trials—CR vs. 50% of trials—PR) to 2 pellets in the postshift phase, or exposed to 2 pellets throughout the training. The results indicated that the iSNC only appeared in RLA-I rats exposed to CR, as opposed to RLA-I animals exposed to PR and to RHA-I rats exposed to PR or CR. These data seem to support the implication of emotional responses in both iSNC and PR situations, and indicate that the behavioral reactivity to reward loss experiences is modulated by genetic variables.